A Study On The Effect Of Overfill Design On The Structural Behaviour Of Precast Concrete Closed Spandrel Arch Bridge - Gan, Ka Jing (Universiti Sains Malaysia, 2018)
Arch bridges are gaining popularity since the introduction of precast concrete technology. Closed spandrel arch bridge is one type of precast arch bridge that consists of earth materials that is filled between the spandrel walls and the top of the precast arches. Among the backfilling materials, lean concrete is good in providing strength and rigidity for the arch, yet it comes with a higher cost. In order to achieve a more economical design, it is crucial to understand the structural behaviour of the precast concrete arch under different overfill design. Three types of models have been analysed including model with varying thickness of lean concrete overfill along the arch, model with varying thickness of lean concrete buttress support built adjacent to the end of the arch and model with interchange of soil and lean concrete layers backfill and different cut slope distance. The analysis was carried out using finite element analysis software, PLAXIS. The axial force, shear force, bending moment and deflection of the arch for different models were observed. It is found that models with lean concrete fill along the arch are effective in reducing the overall forces and bending moment while models with lean concrete buttress support are effective in reducing the maximum shear forces and hogging moment only. On the other hand, the models with interchange of lean concrete and soil layer backfill are inducing higher forces and bending moment to the arch. The cost reduction of steel reinforcement required and cost for replacement of soil fill with lean concrete was also calculated to estimate the effectiveness of the model. The model with lean concrete of 400mm thick at support and 100mm thick at crown lying along the arch panel and model with lean concrete buttress support of 1.0m width and 1.0m height show the highest reduction of cost required.